Poly(para-phenyleneethynylene)s as emitters in polymer LEDs - Smarsly, Emanuel; Daume, Dominik; Braig, Felix; Koser, Silke; Dörsam, Edgar; Bunz, Uwe H. F. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2018)
11 different dialkoxy- and dialkyl-poly(para-phenyleneethynylene)s (PPEs) featuring novel branched and literature described linear and branched side chains were prepared using a Sonogashira coupling. The side chains were of different length and branching character. The degree of polymerization of the PPEs ranged from Pn = 44-343 with polydispersities ranging from 1.5-3.1. Fairly simple OLED-stacks with up to three layers (electron injection, emitter layer, and hole injection) were produced. Depending upon the PPEs’ structure and the stack architecture but particularly the thickness of the emitting PPE-layer, a large increase in brightness up to 2.2 × 103 cd m−2 was observed, a significant improvement over earlier reported values.
Gesehen am 13.12.2019